The spatial maturity of Dutch towns: A comparative analysis of the emergence of the outlines of the Randstad, with reference to town maps (OverHolland, 2017)
In the eleventh, twelfth and thirteenth century the Dutch landscape underwent a major spatial transformation. In a relatively short space of time, large areas of hitherto inaccessible peatland were reclaimed and made suitable for agriculture and habitation. In the thirteenth and fourteenth century this was quickly followed by urbanisation. The urbanisation process was remarkably rapid, and a great deal has already been written about the growth of Dutch towns. However, the emphasis has mainly been on administrative, economic and social changes during this period. Studies of the spatial dimension, especially comparative ones, have been rare.